Implementasi Standar Sarana dan Prasarana Melalui Regulasi Permendiknas 24/2007 Di SMPN 1 Belitang - Dewimah Putri Tazkiyah; Sedya Sentosa; Nadilla Aleyda Maqhfira Agustin (CV. ITTC INDONESIA, 2025)
This research is motivated by the suboptimal implementation of Education Facilities and Infrastructure Standards as regulated in Minister of National Education Regulation Number 24 of 2007, which remains a challenge in various educational units, including at SMP Negeri 1 Belitang. The objective of this study is to describe the level of conformity in the implementation of facilities and infrastructure standards at the school and to analyze the internal and external factors influencing it. This research employs a qualitative method with a case study approach. Data were collected through interviews, observations, and documentation with the school principal, the vice principal for curriculum, and subject teachers. The research findings indicate that most facilities and infrastructure meet the standards, such as classrooms, computer laboratories, and digital facilities, although the science laboratory and counseling room remain limited. The main supporting factors for successful implementation include collaborative leadership, community participation, and transparent utilization of BOS and DAK funds. This study concludes that the effectiveness of education facility management depends on a participatory culture, digital innovation, and sustainable governance aligned with national education policies.